Bonding heterogeneity in mixed-anion compounds realizes ultralow lattice thermal conductivity. Issue 39 (4th October 2021) - Sato, Naoki; Kuroda, Norihide; Nakamura, Shun; Katsura, Yukari; Kanazawa, Ikuzo; Kimura, Kaoru; Mori, Takao
Abstract : Bonding heterogeneity in mixed-anion chalcohalides derives ultralow lattice thermal conductivity despite their low averaged atomic mass. Abstract : Crystalline materials with intrinsically low lattice thermal conductivity ( κ lat ) pave the way towards high performance in various energy applications, including thermoelectrics. Here we demonstrate a strategy to realize ultralow κ lat using mixed-anion compounds. Our calculations reveal that locally distorted structures in chalcohalides MnPnS2 Cl (Pn = Sb, Bi) derive bonding heterogeneity, which in turn causes a peak splitting of the phonon density of states. This splitting induces a large amount of scattering phase space. Consequently, the κ lat of MnPnS2 Cl is significantly lower than that of a single-anion sulfide CuTaS3 with a similar crystal structure. The experimental κ lat of MnPnS2 Cl takes an ultralow value of about 0.5 W m −1 K −1 at 300 K. Our findings will encourage the exploration of thermal transport in mixed-anion compounds, which remains a vast unexplored space, especially regarding unexpectedly low κ lat in lightweight materials derived from bonding heterogeneity.